A survey: comparative study on internet of things and cloud of things. (28th November 2019) - Mohanasundaram, R.; Brindhadevi, Kathirvel; Kumar, Navin; Mule, Rishikesh Y.
In today's era, an exponential rise in technology is changing our lives essay. Tens of millions of devices are getting connected to the internet every day. This extensive growth of the internet and increasing number of interconnected devices has given a rise to many new-age technologies. The internet of things (IoT) provides an innovative means of communication amongst these new-age technologies and the web world. Cloud computing enables a convenient, on demand and scalable network access to a shared pool of configurable computing resources. Integrating cloud computing with internet of things brings the concept of cloud of things. The cloud of things framework is based on a combination of ubiquitous distributed sensing units, outcomes stored in the cloud for awareness. This paper surveys a comparative study on internet of things and cloud of things demonstrating how cloud of things has prevalent benefits over internet of things. Also, this paper explains how introduction of fog computing concept in cloud and IoT improves efficiency of cloud of things.